(untitled) (Quinto Sol, 2022)
This paper presents and analyzes politics in the context of its independence declared in 1820. It considers the local and regional dimension as spaces of action and projection of La Rioja’s elite and identifies the influence of its political construction as an explanatory element. This path of analysis helps to understand the centrality that Facundo Quiroga acquires in the construction of the province, with regard to the region.